Yield Response of Abelmoschus Esculentus as Influenced by Compost With Tithonia Leaves - Samarakoon, S.G.N.D.; Seran, Thayamini H. (International Journal of Environment, 2023)
Tithonia diversifolia is a genus of flowering plants and its leaves have been used to improve fertility and soil properties by supplying organic matters and nutrients. This experiment was done to study the effect of compost with powdered Tithonia leaves on okra yield and to select the optimal quantity of Tithonia leaves for obtaining the optimum yield of okra in the sandy regosol soil conditions. This experiment was carried out in a completely randomized design with five replicates with the following treatments; T1 - recommended chemical fertilizers (control), T2 - compost 140 g alone, T3 - compost 140 g + 15 g powdered Tithonia leaves (PTL), T4 - compost 140 g + 30 g PTL, T5 - compost 140 g + 45 g PTL, T6 - compost 140 g + 60 g PTL. These fertilizers were applied as the basal application to each polybag (0.07 m2), while the top dressing was not applied in this experiment. The results revealed that compost with PTL application had effects on the number of pods per plant, the number of seeds per pod, pod length, pod girth, single pod weight, fresh pod weight per plant and marketable pod yield. Further, it was found that T4 was more suitable for obtaining a better marketable pod yield of okra in sandy regosol soil conditions. Based on the results obtained, it can be concluded that 2 kg m-2 compost with 0.43 kg m-2 powdered Tithonia leaves as the basal application could be used in okra cultivation.